The development of a self-report outcome measure to assess social participation restrictions in adults with hearing loss - Heffernan, Eithne (2017)
Hearing loss is a widespread condition that can substantially affect not only auditory functioning but also social functioning. Therefore, it is essential to demonstrate that auditory rehabilitation can improve social participation in individuals with hearing loss. However, currently, there is a lack of agreed-upon, gold-standard, hearing-specific outcome measures.